2016
DOI: 10.1002/dvg.22915
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome engineering in zygotes with CRISPR/Cas9

Abstract: SUMMARYDeletions, duplications, and inversions of large genomic regions covering several genes are an important class of disease causing variants in humans. Modeling these structural variants in mice requires multistep processes in ES cells, which has limited their availability. Mutant mice containing small insertions, deletions, and single nucleotide polymorphisms can be reliably generated using CRISPR/Cas9 directly in mouse zygotes. Large structural variants can be generated using CRISPR/Cas9 in ES cells, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 24 publications
1
68
0
1
Order By: Relevance
“…Over the course of this experiment, we also obtained mice carrying a 5 Mb inversion but no duplications were obtained [32]. Boroviak et al [33] also reported that they microinjected Cas9/two sgRNAs and ssODN as a donor to guide deletion in fertilized eggs and detected 1.1 Mb deletions and inversions in 30 and 21% of embryos genotyped, respectively, although no duplications were observed. When they tried to generate 155 and 545 kb rearrangements using the same strategy, only 1-2% of mice analyzed had the duplication, while 18-24 and 18-30% of mice contained deletions and inversions, respectively.…”
Section: Reproduction Of Diseases In Mice Carrying Chromosome Rearranmentioning
confidence: 63%
“…Over the course of this experiment, we also obtained mice carrying a 5 Mb inversion but no duplications were obtained [32]. Boroviak et al [33] also reported that they microinjected Cas9/two sgRNAs and ssODN as a donor to guide deletion in fertilized eggs and detected 1.1 Mb deletions and inversions in 30 and 21% of embryos genotyped, respectively, although no duplications were observed. When they tried to generate 155 and 545 kb rearrangements using the same strategy, only 1-2% of mice analyzed had the duplication, while 18-24 and 18-30% of mice contained deletions and inversions, respectively.…”
Section: Reproduction Of Diseases In Mice Carrying Chromosome Rearranmentioning
confidence: 63%
“…Speciically, it may ofer opportunities to obtain mutants for other less commonly used animal models by direct zygote injection of the CRISPR/Cas9 components without involving ES cells [12][13][14]. This new approach may also facilitate chromosome engineering in mice from diferent strain backgrounds than those currently available with the Cre/loxP-mediated ES cell methods [7,8]. Furthermore, it may lead to the generation of desired animal models more quickly.…”
Section: The Potential Advantages Of Crispr/cas9-facilitated Chromosomentioning
confidence: 99%
“…Furthermore, it may lead to the generation of desired animal models more quickly. Table 1 summarized the eiciencies of three types of structural variations, deletion, inversion, and duplication, in mouse [7,8].…”
Section: The Potential Advantages Of Crispr/cas9-facilitated Chromosomentioning
confidence: 99%
See 1 more Smart Citation
“…Now, the combination of chromosome transfer and genome editing technology is crucial for the efficient production of fully humanized animal models (Fig. 4) [76]. If genome editing of KO endogenous genes can be applied to germlinetransmitted Tc animals, both time and cost for mating Tc and KO animals will be saved.…”
Section: Humanized Animal Model: the Cyp3a Model Mousementioning
confidence: 99%